Estimation of Ion Temperature in the Upper Ionosphere Along the Swarm Satellite Orbits - L. Lomidze (American Geophysical Union (AGU), 2021)
Abstract Ion temperature is one of the key parameters that provides insight into the thermal balance of the coupled ionosphere‐thermosphere system. Together with the temperatures of neutral and electron gases, it affects physical and chemical processes and parameters in the upper atmosphere. These include the ion‐neutral collision frequencies, chemical reaction rates and plasma scale height, all of which influence the variation and distribution of ionospheric plasma. The European Space Agency's three, nearly polar‐orbiting Swarm satellites at about 500 km altitude measure ionospheric electron temperature, density, and ion drifts using electric field instrument (EFI) Langmuir probes and Thermal Ion Imagers. Measurements of the ion temperature, though initially planned, are not available due to technical problems with the ion imagers. This paper describes a model that estimates the ion temperature along the orbits of Swarm satellites and evaluates the validity of the corresponding data. This data‐driven, physics‐based model combines an ion heat balance equation of the upper ionosphere, the Swarm EFI measurements, and empirical models for neutral composition, winds, and electric field. The validity of this approach was investigated using a physics‐based ionosphere model (SAMI3) for different geophysical conditions. We have studied the effects of various assumptions and input data limitations to the model accuracy, and have validated the estimated ion temperature against independent measurements from low, middle, and high‐latitude incoherent scatter radars (ISRs). When compared with the ISR data, the obtained Swarm‐based ion temperature shows small systematic errors (1%–2%), high correlations (Swarm A/C 0.8, Swarm B 0.6), and random errors of 10%–20%.